UV Spectrophotometric Estimation of Voriconazole in Bulk and Tablet Dosage Form - Jain, Anurekha; Maliwal, Deepika; Patidar, Vidyasagar; Joshi, Anirudh (Asian Journal of Chemistry, 2010)
A new simple, rapid, sensitive and precise spectrophotometric method in ultra violet region has been developed for determination of voriconazole in bulk and tablet dosage form. Voriconazole exhibited maximum absorbance at 256 nm with apparent molar absorbitivity of 1.636E + 04 in 0.1 N HCl. Beer's law was found to be obeyed in the concentration range 10-70 mcg/mL. Regression equation was found to be 0.034105x - 0.46707 and coefficient of correlation was 0.9986. The proposed method is sensitive, accurate, reproducible and useful for the routine estimation of voriconazole in bulk.